A new naidid oligochaete species (Annelida, Clitellata, Naididae) from Vietnam with asexual reproduction by fragmentation - Gusakov, Vladimir A. (Zootaxa, 2021)
A new oligochaete of the family Naididae, subfamily Naidinae, Bratislavia gusevi sp. n., was found in a forest stream in Vietnam. The worm is characterized by small size, asexual reproduction by fragmentation, and dorsal bundles of chaetae beginning from segment II. Each dorsal bundle bears one to two hairs and one to two simple-pointed or bifid, rarely trifid, needle chaetae. An additional distinctive feature of the worm is the presence of one to two enlarged simple-pointed needle chaetae in the bundles of segment IV. These chaetae are somewhat longer and markedly wider than the needles in the rest of the segments. The present paper provides an illustrated description of the discovered individuals and discusses the species’ systematic position, asexual reproduction and regeneration.